Assessing self-perceptions related to safe medication management among nursing students: an analytical cross-sectional study in Iran - Reza Nemati-Vakilabad; Maryam Hashemian; Mohammad Reza Mojebi; Alireza Mirzaei (BMC Nursing)
Abstract Background Ensuring patient safety is critical, with safe medication management being a key aspect. However, nursing students often lack the necessary skills for effective medication management. These students need to acquire the required competencies during their undergraduate studies. Objective This study aimed to investigate the self-perceived status of Iranian nursing students in medication safety management. Design An analytical cross-sectional study. Method The study involved 221 nursing students who completed surveys assessing their self-perception of drug management and dosage calculation. Demographic data were also collected. The data collection forms included a self-perception questionnaire and a dosage calculation test. Analytical tests such as independent sample t-tests, one-way ANOVA, Pearson’s correlation coefficient, and descriptive statistics were employed for data analysis using SPSS 22.0 software. Results Our research found that the average self-perception score of students in medication management was 57.65 ± 13.53 (range = 24–96). Linear regression analysis revealed that higher overall GPAs (F = 38.098, p < 0.001) and work experience in a hospital (t = 10.367, p < 0.001) were associated with improved self-perception skills in medication management. Additionally, individuals with increasing age demonstrated better self-assessment skills in managing safe medications. Conclusion This study underscores the importance of nursing education in enhancing students’ competencies in safe medication management. Specific interventions are recommended to improve knowledge and skills, and sociodemographic factors can help identify students needing additional support. Increasing clinical exposure is also suggested to enhance their competencies.